Trial by Jury in Russian Military Courts - Nikolai P. Kovalev (Journal of Power Institutions in Post-Soviet Societies, 2008)
One of peculiar features of the military criminal justice system in Russia is that in some cases military defendants may apply for trial by jury. Unlike the existing U.S. court-martial jury and the Russian military jury of the early 1900s (World War I period) which were comprised of the members of the armed forces, in modern Russia jurors trying military defendants are civilians. This article aims to provide a brief history of military jury in Russia and identify issues of independence and impartiality in Russian military courts with participation of lay decision-makers. In particular, the article will analyze two high-profile cases which resulted in acquittals of Russian officers accused of killing several Chechen civilians during counter-terrorist operations in Chechnya.